Does Digitally Enabling Frontline Health Workers Improve Coverage and Quality of Maternal and Child Health Services? Findings From a Mixed Methods Evaluation of TECHO+ in Gujarat - Saha, Somen; Quazi, Zahiruddin Syed (Frontiers in Public Health, 2022)
Introduction Technology Enabled Community Health Operations (TeCHO+) is a mobile and web-based application (app) for frontline health workers. It includes features such as real-time data entry, automated generation of the work plan, and a decision support system generating alerts for high-risk cases. Since 2019, the programme is implemented across all 33 districts of Gujarat, catering to a population of over 60 million. This study aims to compare changes in the coverage, quality of data reporting maternal and child health services, and time spent in the documentation before and after the introduction of the TeCHO+ app. Methods To address the study aim, a mixed-method design with a realist evaluation approach was adopted. The survey was conducted with randomly selected beneficiaries from 32 sub-centers across two districts of Gujarat State in India. We surveyed 215 postpartum women and mothers of 102 children at baseline (pre) and 246 postpartum women and mothers of 119 children post 1 year of the TeCHO+ programme intervention in 2020. For qualitative data, total 29 Auxiliary Nurse Midwives, 12 Data Entry Operators and 10 Primary Health Center Medical Officers were purposively selected from 32 PHCs and interviewed to understand the pathways leading to the programme outcome. Results Following introduction of TeCHO+, the coverage of full antenatal care (ANC; 75.6% vs. 67.9%, p-value < 0.0001), consumption of at least 180 iron-folic acid tablets (93% vs. 77%, p-value < 0.001), early initiation of breastfeeding (42.7% vs. 24.2%, p-value < 0.001), five home-visits by ANM during the first month after delivery (36.2% vs. 27.9%, p-value = 0.056), HBV0 vaccination (67.2% vs. 35.3%, p-value < 0.0001) and Pentavalent 2 (100% vs. 95.1%, p-value = 0.015) improved. The overall concordance rate for routine maternal health indicators (a measure of data quality) improved from 69.1 to 80.5%, while that for routine child health indicators improved from 86.6 to 92.1%. The programme resulted in 1.7 h saving a day of ANM's productive time and 1.5 h (a day) of data entry operator's time. Conclusions The TeCHO+ programme has improved access to care. It impacted both coverage of maternal and child health services and data reporting quality of various maternal and child high-risk conditions. Considering the programme's success, other disease services might be added to the scope of TeCHO+ software.